Engineering of mixed Bi₄(GexSi₁₋x)₃O₁₂ scintillation crystals - Galenin, E.; Biatov, M.; Gerasymov, I.; Grinyov, B.; Sidletskiy, O.; Baranov, V.; Budagov, J.; Davydov, Yu.; Glagolev, V. (Functional Materials, 2015)
A full range of BGSO crystals from BGO to BSO was grown by the Czochralksi method. A set of procedures such as changing of stoichiometry, recrystallization and thermal treatment was applied to improve optical and scintillation parameters of the crystals. The relationships between scintillation yield, energy resolution, decay constants and Si⁴⁺/Ge⁴⁺ ratio in the crystals are discussed with regard to ongoing experiments on high energy physics. Crystal composition with better energy resolution 16.2 % at 662 keV irradiation was obtained.